Reforming water allocation policy through markets in tradable water rights: lessons from Chile, Mexico, and California - Rosegrant, Mark W.; Gazmuri, Renato (International Food Policy Research Institute, 1994)
Increasing water scarcity, rising costs of irrigation subsidies, and general economic liberalization are creating strong incentives for comprehensive water reform with establishment of tradable water rights and the development of markets in these rights. Experiences in Chile, Mexico, and California indicate that water allocation through markets in tradable water rights offers a viable approach to improving the efficiency of water allocation, and should receive serious consideration from developing country policy makers. Laws establishing tradable rights should be simple and comprehensive, should clearly define the characteristics of water rights and the conditions and regulations governing the trade of water rights; should establish and implement water rights registers; delineate the roles of the government, institutions, and individuals involved in water allocation and the ways of solving conflicts between them; and provide cost-effective protection against negative third party and environmental effects which can arise from water trades.